Pengaruh Gaya Hidup Berbelanja Online, Kemasan Serta Negara Asal Terhadap Keputusan Pembelian - Yosua Anugerah Mogea; Sujana Sujana (LPPM IBI Kesatuan, 2022)
This study aims to determine whether the Online Shopping Lifestyle, Packaging, and Country of Origin influence partially and simultaneously on Purchasing Decisions. The population in this study are consumers who have bought at Starbucks Bondongan, Bogor city with a total sample of 250 people. The sampling method used is a non probability sampling method with the type of purposive sampling. The data analysis method uses multiple linear regression to determine the effect of the Online Shopping Lifestyle, Packaging, and Country of Origin on Purchasing Decisions. Data testing was performed using SPSS 20. The results of this study are as follows: (1) The results of multiple regression analysis produce a regression equation: Y = 0.94 + -0.07X1 + 0.132X2 + 0.666X3 + Error or Purchase Decision = 0,94 + -0,07 Lifestyle Shopping Online + 0,132 Packaging + 0,666 Country of Origin. Through this equation it is concluded that every increase or increase of 1 unit in the variables X1, X2, and X3 then Y will increase. While the coefficient of determination (R Square) generated is equal to 0.660 which means that the independent variables (Lifestyle Shopping Online, Packaging, and Country of Origin) have the ability of 65% in explaining the variation of the dependent variable (Purchasing Decision). (2) The simultaneous effect of the three independent variables on the dependent variable is significant as indicated by the calculated F value = 8.239 and the significance value = 0.000. The calculated F value obtained is greater than F table 4.22 and the significance value obtained is less than 0.05 or 5%, so it can be stated that the independent variables (Online Shopping Lifestyle, Packaging, and Country of Origin) together have a significant effect on the dependent variable (Purchase Decision). (3) Variable X1 (Lifestyle Shopping Online) obtained t count of 0.0186 smaller than t table 1.65 and a significance value of 0.0853 or 8.53% greater than 0.05 or 5%, so it can be stated that variable X1 partially (individually) has no effect on the variable Y (Purchase Decision). (4) Variable X2 (Packaging) obtained t count of 2.481 is greater than t table 1.65 and the significance value of 0.014 or 14% is greater than 0.05 or 5%, so it can be stated that the variable X2 partially (individually) influences variable Y (Purchase Decision). (5) Variable X3 (Country of Origin) obtained by t count of 14.416 is greater than t table 1.65 and a significance value of 0.000 or 0% is less than 0.05 or 5%, so it can be stated that the variable X3 is partially (individually ) affect the variable Y (Purchase Decision). Keywords: Online Shopping Lifestyle, Packaging, Country of Origin and Purchasing Decisions